Worker smiles as she bags - Ferrendelli, Betta (Raton Range Raton, NM, 1992)
This article is about Maureen Krulyac who works for Super Save Discount Foods.
Newspaper article + Photograph of Maureen Krulyak
Master list item #: 82
File location is in the Raton file Cabinet
Keywords: Krulyac, Maureen; Archuleta, Henry; Supersave Discount Foods; Anthony Jewelers; Business History; Workers; Courtexy Clerks; Raton, New Mexico